Identity, Politics and Nation: Algerian Nationalism and the 'Berberist Crisis' of 1949. Issue 2 (2nd April 2016) - Fois, Marisa
Abstract: Between the 1940s and the 1950s, a crucial period of change for Algerian nationalism and state formation, Berber activists within the anti-colonial nationalist movement challenged the political line of the nationalist party, the Mouvement pour le Triomphe des Libertés Démocratiques . This opposition focused on the need to redefine the concept of identity: activists did not reject either Arabic or Islam—the dual linguistic-religious core of national identity for Algerian nationalists—but they identified with a broader idea of an 'Algerian Algeria' that could incorporate various components of society. Through the study of archival sources, this paper analyses the origins and consequences of the 1949 controversy within Algerian nationalism known as the 'Berberist crisis'. Particular attention is paid to the idea of the nation proposed, assessing whether and how Berber activists participated in the political debate and state-building.